THE INFLUENCE OF FOLIC ACID ON THE RATE OF H2O2 DECOMPOSITION IN ALKALINE AND ACIDIC AQUEOUS SOLUTIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The action of folic acid (FA) has been studied on the reaction H2O2+HOO–, which occurs in alkaline and H2O2+Fe(II), which occurs in acidic aqueous solutions. It has been established that in both cases FA decreases the rate ($W_{O_2}$) of H2O2 decomposition. The increase of [FA]0 results in decrease of $W_{O_2}$ in alkaline medium. It is concluded that FA (its anion) acts on $W_{O_2}$ of H2O2 decomposition, which occurs by radical-chain mechanism. An unusual phenomenon is also noticed. During the reaction in alkaline medium approximately 1 min the reaction is stopped, then it begins to run again, but with a decreased rate. It is assumed that during the reaction a compound is formed by radical mechanism, which reacts with O2. The tablets of FA which are for sale in pharmacies contain a definite quantity of starch. For this reason its influence on the reactions is studied too. It is established that it has no significant influence on the reactions’ rates in both cases.
Keywords: folic acid; radical-chain mechanism; reactions’ rates; alkaline medium